Digital Marketing Strategy In The Era Of E-Commerce: Winning The Competition - Utamirohmahsari; Anurak Boonyarit; Siti Zulaikha (JMEB Jurnal Manajemen Ekonomi & Bisnis, 2026)
The rapid evolution of technology has revolutionized the business landscape, particularly within the e-commerce sector. E-commerce has become an integral part of daily life, driving online sales growth and expanding market reach. This article explores the development and impact of e-commerce applications on bolstering online sales, with a focus on Indonesia's digital economy. Through a comprehensive literature review and analysis, the study highlights the importance of user-centric design methodologies, personalized user experiences, and the integration of artificial intelligence in e-commerce applications. Furthermore, it discusses the significance of efficient promotional strategies and the role of consumer behavior analysis in enhancing sales efficacy. Despite the challenges posed by security concerns and logistical limitations, the article emphasizes the immense potential of e-commerce in Indonesia's digital economy. By innovating and adapting to technological advancements while addressing existing challenges, businesses can capitalize on the opportunities presented by the burgeoning e-commerce landscape, fostering sustainable growth and competitiveness.